2020
DOI: 10.1155/2020/1860219
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Statistical Analysis Reveals the Heterogeneity of Lacustrine Tight Oil Accumulation in the Middle Permian Jimusar Sag, Junggar Basin, NW China

Abstract: Tight oil and gas accumulation commonly has heterogeneities within the reservoir formation. This heterogeneity, however, is hard to investigate by conventional geological and (organic) geochemical tools and thus is critical and challenging to study. Here, we attempted multivariate statistical analysis to reveal the heterogeneity based on a case study in the lacustrine tight oil accumulation in the middle Permian Lucaogou Formation of the Jimusar sag, Junggar Basin, NW China. Clustering heat maps and multi-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The variable oil density might be related to the complex organic inorganic–interaction during hydrocarbon generation. First, haloduric algae have been universally acknowledged for highly efficient and prolonged oil generation compared with those freshwater algae. , Second, the effects of carbonate and biocarbonate minerals on hydrocarbon generation and expulsion of source rocks are really complex. It was found that pyrolysis reactions are catalyzed by alkali and alkaline earth metal cations, resulting in more hydrocarbons generating from kerogen. Meanwhile, hydrocarbon expulsion appears to be retarded due to the absorption of carbonate minerals, which results in more heavy components of hydrocarbon that generated at earlier stage retained in the source-rock sequences whereas lighter compounds prefer to be expelled .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variable oil density might be related to the complex organic inorganic–interaction during hydrocarbon generation. First, haloduric algae have been universally acknowledged for highly efficient and prolonged oil generation compared with those freshwater algae. , Second, the effects of carbonate and biocarbonate minerals on hydrocarbon generation and expulsion of source rocks are really complex. It was found that pyrolysis reactions are catalyzed by alkali and alkaline earth metal cations, resulting in more hydrocarbons generating from kerogen. Meanwhile, hydrocarbon expulsion appears to be retarded due to the absorption of carbonate minerals, which results in more heavy components of hydrocarbon that generated at earlier stage retained in the source-rock sequences whereas lighter compounds prefer to be expelled .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, linear dimensionality reduction has considerable limitations, particularly when analyzing the geochemical characteristics of hydrocarbons in complex petroleum systems. A relatively low fitting accuracy is obtained when the higher-dimensional relationships of such data are characterized using the linear dimensionality reduction approach, and may yield results that are geologically unreasonable …”
Section: Samples and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the Permian shale oil exploration in the Junggar Basin has made major breakthroughs (e.g. Cao et al, 2020;Li et al, 2021;Wang et al, 2020a;Wu et al, 2016Wu et al, , 2017. Among them, the organic-rich Lucaogou Formation, a unique lacustrine mixed depositional sequence composed of terrigenous clastic, carbonate minerals, and volcaniclastic sediments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The chemometric method can simultaneously process the measured parameters or variables based on multivariate statistical treatments. Therefore, this method has been widely used in several disciplines after its development in only a few decades (Bevilacqua et al, 2017;Chabukdhara and Nema, 2012;Madsen et al, 2010;Wang et al, 2020); however, its application in the field of petroleum geochemistry began in the 1980s (Kvalheim et al, 1985;Øygard et al, 1984;Peters et al, 1986;Telnaes and Dahl, 1986;Zumberge, 1987).…”
Section: Introductionmentioning
confidence: 99%